2017
DOI: 10.1590/1678-4324-2017160128
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Soybean Seedlings Upon Nutrient Application by Seed Coating

Abstract: The aim of this study was to evaluate the effect of different seed coatings consisting of various combinations of three nutrients (calcium, magnesium and silicon) on two soybean cultivars (BRS 243 RR and CD 233 RR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Although, positive and significant results are verified in the production of SDM, being the data adjusted to a quadratic behavior, where the maximum point of dry matter accumulation was at the dose of 100g Si 100 kg -1 of seeds, resulting in the increase of 16% in relation to zero dose (Table 1). These results agree with other studies, which demonstrated that Si is a benefic element, that positively influences the growth rate and seedling development at initial stages when supplied with seeds coating (Tavares et al, 2012;Tunes et al, 2014;Corlett et al, 2014;Janmohammadi & Sabaghnia, 2015;Rufino et al, 2017).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Although, positive and significant results are verified in the production of SDM, being the data adjusted to a quadratic behavior, where the maximum point of dry matter accumulation was at the dose of 100g Si 100 kg -1 of seeds, resulting in the increase of 16% in relation to zero dose (Table 1). These results agree with other studies, which demonstrated that Si is a benefic element, that positively influences the growth rate and seedling development at initial stages when supplied with seeds coating (Tavares et al, 2012;Tunes et al, 2014;Corlett et al, 2014;Janmohammadi & Sabaghnia, 2015;Rufino et al, 2017).…”
Section: Resultssupporting
confidence: 93%
“…The adequate management with mineral nutrients supplying, throughout the technique of seeds coating, allied to physic, physiologic, genetic and sanitary quality, propitiate vigorous plants, with adequate and uniform stand. The seeds, by its nature, will have better performance in adverse environmental conditions, in this manner, being fundamental to obtain appropriate yield levels (Corlett et al, 2014;Mondo, Nascente, & Cardoso Neto, 2016;Rufino et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the optimal Si doses of 102, 97 and 100 g, an expectation of dry matter increases of 37, 30 and 36% for MSPA, MSR and MSTP, respectively, compared to zero (Table 2). These results corroborate with other studies, which demonstrate that Si is a beneficial element and that it positively influences the growth rate and the development of seedlings in the initial stages, when provided via covering (CORLETT et al, 2014;RUFINO et al, 2017;TAVARES et al, 2012).…”
Section: Resultssupporting
confidence: 92%
“…Seed germination is known to be one of the most important stages in plant development, during this period several factors can interfere with a rapid and uniform emergence. Seed coating with silicon (Si) may be an alternative to improve field seed and seedling performance when subjected to adverse environmental conditions (RUFINO et al, 2017).…”
Section: Introductionmentioning
confidence: 99%